Adherence and factors related to acceptance of alcohol for antiseptic hand rubbing among nursing professionals - Adriana Cristina de Oliveira; Camila Sarmento Gama; Adriana Oliveira de Paula
Abstract OBJECTIVE Identify rates of adhesion and related factors to acceptance of an alcohol based preparation to hands antiseptic friction among nursing professionals in a unit of intensive therapy. METHOD A cross-sectional study, which involved direct observation of hand hygiene opportunities and nursing professionals' completion of questionnaires, was conducted at a university hospital between January and July 2015. Descriptive and univariate analyses were performed, with a 5% significance level. RESULTS It was observed 956 opportunities of hand hygiene among 46 nursing professionals. The rate of adhesion to alcohol-based handrub (ABH) was 34.8% and about 87.0% preferred handwashing. Nurses used ABH more frequently than nursing technicians (p <0.001), and the report of feeling of clean hands after using the alcohol product was directly related to higher rates of adherence to antiseptic friction through observation (P <0.05). CONCLUSION The finding indicating low ABH usage highlights the need for greater institutional investment in strategies that help health professionals to recognize the advantages of this type of HH with respect to time spent, ease of access to dispensers, effectiveness in eliminating microorganisms, and maintaining skin moisturization.